Residential Housing Quality Assessment Based on the Criteria of Sustainable Housing (Case Study: Residential Complex of 100 Units of Region 1 City of Zahedan) - Saberi, Farzaneh; Miri, Gholam Reza; Zadeh, Masume Hafez Reza (International Journal of Geography and Geology, 2016)
The most basic human needs throughout history, is the need for housing. On the other hand, in recent years one of the topics that were of interest to scholars and experts, is the quality of life and environment. Lack of attention to the physical-spatial standards in the design of residential complexes can cause major problems in the field of housing and living conditions. This study examines the criteria for sustainable housing in the city of Zahedan and in a complex-residential area. The statistical population is 19080 people in the city of Zahedan in a residential area, and the sample was calculated using a sample of 318 people, Library and field is the method of studying and using a questionnaire. And to analyze the data, one sample T-test has been used in SPSS software, and to rank the residential complexes of entropy the hierarchical analysis model is used. The results of the one-sample T-test indicates that housing indicators in terms of physical, social and environmental terms are not in good condition. Considering that the average 3 is calculated from the test T, (67/2, 87/2, 49/2) are lower than the basis of the standards. The mean difference in level is more than 99% and it is statistically significant and reliable (Sig = 0.000).